Weak effects of birds, bats, and ants on their arthropod prey on pioneering tropical forest gap vegetation - Piotr Szefer; Kenneth Molem; Austin Sau; Vojtech Novotny (Ecology, 2022)
The relative roles of plants competing for resources versus top‐down control of vegetation by herbivores, in turn impacted by predators, during early stages of tropical forest succession remain poorly understood. Here we examine the impact of insectivorous birds, bats, and ants exclusion on arthropods communities on replicated 5 × 5 m of pioneering early successional vegetation plots in lowland tropical forest gaps in Papua New Guinea. In plots from which focal taxa of predators were excluded we observed increased biomass of herbivorous and predatory arthropods, and increased density, and decreased diversity of herbivorous insects. However, changes in the biomass of plants, herbivores, and arthropod predators were positively correlated or uncorrelated between these three trophic levels and also between individual arthropod orders. Arthropod abundance and biomass correlated strongly with the plant biomass irrespective of the arthropods' trophic position, a signal of bottom‐up control. Patterns in herbivore specialization confirm lack of a strong top‐down control and were largely unaffected by the exclusion of insectivorous birds, bats, and ants. No changes of plant–herbivore interaction networks were detected except for decrease in modularity of the exclosure plots. Our results suggest weak top‐down control of herbivores, limited compensation between arthropod and vertebrate predators, and limited intra‐guild predation by birds, bats, and ants. Possible explanations are strong bottom‐up control, a low activity of the higher order predators, especially birds, possibly also bats, in gaps, and continuous influx of herbivores from surrounding mature forest matrix.

Spatial scaling of plant and bird diversity from 50 to 10,000 ha in a lowland tropical rainforest - Richard J. Hazell; Kryštof Chmel; Jan Riegert; Luda Paul; Brus Isua; Graham S. Kaina; Pavel Fibich; Kenneth Molem; Alan J. A. Stewart; Mika R. Peck; George D. Weiblen; Vojtech Novotny (Oecologia, 2021)
While there are numerous studies of diversity patterns both within local communities and at regional scales, the intermediate scale of tens to thousands of km 2 is often neglected. Here we present detailed local data on plant communities (using 20 × 20 m plots) and bird communities (using point counts) for a 50 ha ForestGEO plot in lowland rainforest at Wanang, Papua New Guinea. We compare these local diversity patterns with those documented in the surrounding 10,000 ha of lowland rainforest. Woody plant species richness was lower within 50 ha (88% of 10,000 ha richness), even when both were surveyed with identical sampling effort. In contrast, bird communities exhibited identical species accumulation patterns at both spatial scales. Similarity in species composition (Chao-Jaccard) remained constant while similarity in dominance structure (Bray–Curtis) decreased with increased distance between samples across the range from < 1 to 13.8 km for both plant and bird communities. The similarity decay was more rapid in plants, but in both cases was slow. The results indicate low to zero beta-diversity at the spatial scale represented here, particularly for birds but also for woody plants. A 50 ha plot provided a highly accurate representation of broader-scale diversity and community composition within 10,000 ha for birds, and a relatively good representation for woody plants. This suggests potential for wider generalization of data from ForestGEO plots which are almost always locally unreplicated, at least for those in lowland tropical forest.

Spatial covariance of herbivorous and predatory guilds of forest canopy arthropods along a latitudinal gradient - Ondrej Mottl; Pavel Fibich; Petr Klimes; Martin Volf; Robert Tropek; Kristina Anderson‐Teixeira; John Auga; Thomas Blair; Phil Butterill; Grace Carscallen; Erika Gonzalez‐Akre; Aaron Goodman; et al. (Ecology Letters, 2020)
In arthropod community ecology, species richness studies tend to be prioritised over those investigating patterns of abundance. Consequently, the biotic and abiotic drivers of arboreal arthropod abundance are still relatively poorly known. In this cross‐continental study, we employ a theoretical framework in order to examine patterns of covariance among herbivorous and predatory arthropod guilds. Leaf‐chewing and leaf‐mining herbivores, and predatory ants and spiders, were censused on > 1000 trees in nine 0.1 ha forest plots. After controlling for tree size and season, we found no negative pairwise correlations between guild abundances per plot, suggestive of weak signals of both inter‐guild competition and top‐down regulation of herbivores by predators. Inter‐guild interaction strengths did not vary with mean annual temperature, thus opposing the hypothesis that biotic interactions intensify towards the equator. We find evidence for the bottom‐up limitation of arthropod abundances via resources and abiotic factors, rather than for competition and predation.